A novel loss-of-function mutation in NRAP is associated with left ventricular non-compaction cardiomyopathy - Zhang, Zhongman; Xu, Kangkang; Ji, Lianfu; Zhang, Han; Yin, Jie; Zhou, Ming; Wang, Chunli; Yang, Shiwei (Frontiers in Cardiovascular Medicine, 2023)
Background The nebulin-related-anchoring protein (NRAP) gene encodes actin-associated ankyrin. Few studies reported the association of the NRAP gene with cardiomyopathy. Thus, the genetic role of this gene in cardiomyopathy remains to be investigated. Methods The clinical data of the rare case of left ventricular non-compaction (LVNC) were collected and analyzed. Whole-exome sequencing (WES) was performed on related family members. Western blot was used to detect the effect of mutation on the NRAP protein expression. The effect of the c.259delC variant on myocardial development was further evaluated in a zebrafish model. Results A novel homozygous frameshift mutation c.259delC of NRAP was found in the proband with LVNC. It was found that c.259delC decreased the expression of NRAP by Western blot. In the zebrafish model, the heart development was affected while knocking out the NRAP gene, which showed pericardial edema. The pathological manifestations were uneven hypertrophy, disordered arrangement of cardiomyocytes, enlarged intercellular space, and loose muscle fibers. RNA-sequencing (RNA-seq) showed that the expression of genes related to heart development decreased significantly, and the NRAP gene mutation could participate in biological processes (BPs) such as myocardial contraction, cell adhesion, myosin coarse filament assembly of striated muscle, myosin complex composition, and muscle α-actin binding. Conclusion We identified a rare case of LVNC associated with a novel homozygous NRAP frameshift variant. This study further strengthened the evidence linking mutations in the NRAP gene with LVNC, providing a new clue for further study of LVNC. NRAP may be one of the pathogenic genes of cardiomyopathy.